Pengembangan Aplikasi Kamus Istilah Ilmiah dengan Bahasa Isyarat untuk Peningkatan Kualitas Belajar Siswa Tuna Rungu - Setiawan, Budi Darma; Pradana, Fajar (Indonesian Journal of Disability Studies, 2017)
The government guarantees the absence of a difference for all Indonesian citizens to get education in higher education. Educational needs for every disability is different. Suppose the deaf students, to communicate highly dependent on writing and sign language. From the field observations problems found sign language that is used has a lot of variations, especially for scientific terms such as for example: cell, engineering, photosynthesis and others. This causes the communication becomes slower so that deaf students have difficulty understanding the material taught in the lectures. For that we need to make a media in the form of software to save the new terms as well as sign language. The media should also be accessible though many people (online). This way, if someone is having difficulty in finding a cue for a term, he can look for it on this media. From the results of tests performed, the application is able to enhance the understanding of the time three seconds faster than before using the app. On the usability and user acceptance testing, the application has largely met the expectations of the user.